THE MECHANISMS OF PROFESSIONAL POTENTIAL DEVELOPMENT OF CIVIL SERVANTS IN POLAND - Polishchuk I.V. (Pressing Problems of Public Administration, 2015)
The analysis of modernization processes connected to the professionalization of civil servicein Poland through history has been done. Key principles for the professional potentialdevelopment of civil servants in Poland have been designated within the framework of theirimplementation for the modernization of civil service in Ukraine.